The efficacy of the Domestic Violence Act in reducing gender based violence in rural communities: a case study of Ward 23, Mberengwa District, Zimbabwe - Memo, Addjoy (Midlands State University, 2017)
Gender based violence a global phenomenon a cause for concern, which does not discriminate, knows no race, ethnicity and geographical location, and is a social, economic and a health scourge, a development problem, has bedeviled the achievement of all the Millennium Development Goals. Not until the coordinated approach between the rural and urban, men and women that gender based violence can be totally eradicated. Because gender based violence is inherently gendered, men can be victims as well as perpetrators thus their involvement in the quest to eliminate it as victims, perpetrators, gatekeepers, advocates and activists, is very crucial. In an attempt to align with the international and regional calls for the introduction of measures to eliminate one of the social ills that has held back developmental initiatives, countries have enacted laws which seek to eliminate domestic violence and Zimbabwe was of no exception. The ever increasing cases of domestic violence saw the enactment of the DVA in Zimbabwe in 2007. However to note is how the law is fairly being utilized in the urban areas and rarely in the remote grassroots areas. Thus envisaged in this study is the implementability and utility of the act against a background of social cultural norms and beliefs, poor enforcement mechanisms and unequal prioritization of service provision. The researcher used qualitative research to unpack the efficacy of the Act .The study reveals that GBV is rooted in traditional cultural practices, beliefs and norms, and until these cultural structures are done away with the eradication of gender based violence shall remain a dream in the pipeline especially in the rural areas.